Risk perception and risk communication with regard to nanomaterials in the workplace (Bilbao, 2012)
"Manufactured nanomaterials can bring huge benefits to society but there are concerns about their health and environmental hazards. This literature review shows that there are also serious gaps in the awareness of the potential risks involved in handling manufactured nanomaterials in the workplace, and serious shortcomings in the way that those risks are communicated to the workplace. Effective, transparent, balanced and open risk communication strategies tailored to workplaces are needed to help employers and workers make informed decisions and put adequate prevention measures in place."